Software defined-network for real-time operations of business intelligence tasks - Ibrahim, Awad; Abubakar, Adamu; Zeki, Akram M. (Academik Inspired Network, 2018)
Information and Communication Technology (ICT) is a crucial tool for Business Intelligence. ICT tools help in an operation that yields a "real-time reporting with analytical alert" through the use of BI operation. The efficient handle of the flow of data from one node to the other by BI operation required many network resources, limited resource is a drawback to BI tasks that need a real-time operation. If bandwidth is shared among applications that use the internet. It is consider as one of the crucial obstacles to BI operations. Therefore, a dynamic tasks scheduling application is required. It should be able to manage the flow of data in a network involving of BI operation. For that reason, this paper proposes an effective routing scheme required for BI tasks in order to provide real-time reporting with the analytical decision without link congestion for any task. The proposed mechanism can be used to control the actions and the forwarding rules in the network. This increases the efficiency of a network by rerouting traffics between links. It utilizes the idle links and directs the traffic from and to them to raise the network total efficiency rate. Consequently, bandwidths will be remarkably higher and the link congestion problem will be avoided from that network. In the experiments of emulating congested traffic, the paper gets better network performance of throughput, jitter, and packet loss rate using the proposed traffic rerouting, as opposed to the environment without traffic rerouting.